Pendampingan Tata Kelola Operasional Koperasi - Anjani, Chieka Putri; Septiawati, Ika Teguh; Aziz, Muh. Abdul (Jurnal Surya, 2023)
Cooperative operational governance assistance is a process that aims to assist cooperatives in optimizing their management and operations. This assistance covers various aspects such as the computerization of cooperative members, making organizational structures, and making cooperative operational standards. Several stages must be carried out in the mentoring process, namely surveys, preparation, debriefing, and mentoring. In addition, the companion must also be able to identify the potential and needs of the cooperative to provide appropriate and effective solutions. Cooperative operational governance assistance is expected to help cooperatives improve their performance, improve management systems, and be able to compete with other cooperatives in the market. In the long run. This assistance is expected to improve the welfare of cooperative members, increase income, and increase the contribution of cooperatives to the national economy.